Efektifitas Pendidikan Kesehatan Terhadap Penurunan Nyeri Disminorea Pada Remaja Di SMPN 15 Makassar - Sunarti, Sunarti; Sulastri, Andi; Kamaruddin, Mutmainna; Basniati, Andi (Bunda Edu-Midwifery Journal (BEMJ), 2024)
Background: Dysmenorrhea is menstrual pain felt by women during menstruation, caused by excessive release of prostaglandins. It increases uterine contractions, causing pain during menstruation. Objective: to increase young women's knowledge about disminorhe at SMPN 15 Makassar. Method: This research uses a quasi-experimental type of research with a One Group Pretest and Posttest design. The number of samples as respondents was 20 people taken using total sampling. The research location is at SMPN 15 Makassar. Research results: Analysis using Mc Nemar with p value equal to 0.00 less than 0.05. The level of knowledge before the intervention was given was 16 people (80 percent) had poor knowledge and only 4 people had good knowledge (20 percent), after being given the intervention, only 3 people (15 percent) had poor knowledge and good knowledge increased to 17 people (85 percent). Based on the results of statistical tests, the p value equal to 0.00 less than 0.05, meaning there is a significant influence between providing health education about dysmenorrhea on increasing adolescent knowledge. Health education about dysmenorrhea is effective in increasing the knowledge of young women at SMPN 15 Makassar.